Context-Awareness in Android Application: Context-Aware Personal Financial Assistance (CAPFA) - Mohd Razali, Noor Amanina (Universiti Teknologi PETRONAS, 2011)
This report describes system that examines and reacts to an individual's changing context which can be computer context, user context, or physical context. The author defines mobile computing, context-awareness and financial goals. Integration between these three concept leads to the idea of developing Context-Aware Personal Financial Assistance (CAPFA). This report summarizes the reasons why people fail to achieve their financial goal(s) and how the proposed solution, CAPFA can helps to minimize the rate of failure. CAPFA, an Android context-aware application supports users in managing their financial goal(s). It ensures that user will commit to the financial goal(s) set. The objectives of developing CAPFA are to study how context-aware can be applied in personal financial assistance tool and to develop a context-aware personal financial assistance tool for assisting user in achieving financial goal(s). Software Engineering Process will be the project development guidance from the very beginning to the very end of developing CAPF A. This report describes the hardware and software used, architecture implemented, and functions available.